2000
DOI: 10.1023/a:1008379922120
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study with weekly cisplatin-paclitaxel and concurrent radiotherapy in patients with carcinoma of the cervix uteri

Abstract: The MTD of paclitaxel is 50 mg/m2/wk when associated to cisplatin 30 mg/m2/wk and concurrent pelvic radiotherapy. Diarrhea is the dose limiting side effect. Preliminary data suggest that concurrent chemoradiotherapy with paclitaxel and cisplatin could be a very active treatment for patients with locally advanced carcinoma of the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Moreover, the Taxol/cisplatin combination was effective with respect to both response and survival in the neoadjuvant treatment of LACC and in the palliative treatment of metastatic disease [7]. Recently, a phase I study with weekly cisplatin-Taxol and concurrent radiotherapy reported an overall response of 92% in patients with LACC [8]. Therefore, this study was planned to verify if cytotoxic doses of chemotherapy in combination with conventional radiotherapy could result in improved complete response rates with acceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Taxol/cisplatin combination was effective with respect to both response and survival in the neoadjuvant treatment of LACC and in the palliative treatment of metastatic disease [7]. Recently, a phase I study with weekly cisplatin-Taxol and concurrent radiotherapy reported an overall response of 92% in patients with LACC [8]. Therefore, this study was planned to verify if cytotoxic doses of chemotherapy in combination with conventional radiotherapy could result in improved complete response rates with acceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[23] The same combination was also tried as radio sensitizer in cervical carcinoma and was found to be tolerable and feasible with high response rates. [24][25][26][27][28][29] Chen et al [27] did a phase I study where weekly paclitaxel was combined with 3 weekly cisplatin. The maximum tolerated dose (MTD) of this trial was reported as paclitaxel 50 mg/m 2 /week with cisplatin 50 mg/m 2 once in 3 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum tolerated dose (MTD) of this trial was reported as paclitaxel 50 mg/m 2 /week with cisplatin 50 mg/m 2 once in 3 weeks. There was another phase I study by Pignata et al, [26] which reported cisplatin 30 mg/m 2 and paclitaxel 50 mg/m 2 as the MTD. Both these studies reported tumor response rates more than 90%.…”
Section: Introductionmentioning
confidence: 99%
“…This acts as radiosensitizer and synergistic action along with radiotherapy. [8], [9] Traditional prognostic factors in cervical cancer have been studied. Patients related prognostic factors include age, anaemia and smoking [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%